2012
DOI: 10.1515/bot-2011-0095
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants in mangrove plants and endophytic fungal associations

Abstract: The manner in which fungal endophytes activate host stress response systems is unknown; the occurrence of additional mechanisms involved in symbiotically-conferred stress tolerance in mangrove plants (the primary producers of estuarine food chain) is also an unresolved issue. Here, we report antioxidant potentials of four different mangroves and their endophytic fungi. We elucidated the possible roles of antioxidants in symbiotic association between mangroves and their endophytic fungi. Four different mangrove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 33 publications
4
22
0
1
Order By: Relevance
“…The IC 50 values for DPPH scavenging activities of PEL and AQL were reported as 0.25 and 0.43 mg/ml. The present finding also corroborated the earlier study of Ravindran et al [16] that reported the DPPH radical scavenging potential of methanol leaf extracts of A. officinalis with the EC 50 value of 0.239 mg/ml.…”
Section: In Vitro Antioxidant Activitysupporting
confidence: 93%
See 1 more Smart Citation
“…The IC 50 values for DPPH scavenging activities of PEL and AQL were reported as 0.25 and 0.43 mg/ml. The present finding also corroborated the earlier study of Ravindran et al [16] that reported the DPPH radical scavenging potential of methanol leaf extracts of A. officinalis with the EC 50 value of 0.239 mg/ml.…”
Section: In Vitro Antioxidant Activitysupporting
confidence: 93%
“…The IC 50 value for AQL and PEL were recorded as 0.17 and 0.48 mg/ml respectively. Earlier study also showed that the methanol leaf extracts of A. officinalis exhibited hydrogen peroxide scavenging activity with IC 50 value of 0.378 mg/ml [16].…”
Section: In Vitro Antioxidant Activitymentioning
confidence: 84%
“…The most potent activity was observed with NFW3 (an IC 50 value of 11.7 lg/mL). Antioxidant potential has been reported previously with organic extracts of other fungal endophytes such as Phomopsis, Xylaria and Colletotrichum (Joseph & Priya 2011;Tianpanich et al 2011;Ravindran et al 2012;Wu et al 2013). In addition, Nitya et al (2011) reported DPPH scavenging activities with methanolic extracts of Fusarium, Aspergillus, Penicillium and Mucor, with IC 50 values ranging between 200 and 325 lg/mL.…”
Section: Discussionmentioning
confidence: 66%
“…Conversely, the natural antioxidants present in dietary plants can delay, inhibit, or prevent the oxidation of biomolecules, such as proteins and nucleic acids, and may scavenge free radicals or break the chain reaction due to their redox properties (Dua et al, 2012). An easy, rapid, and sensitive method used to screen antioxidants in plant extracts involves 1,1-diphenyl-2-picryl hydrazyl (DPPH) used in a free radical scavenging assay, and β-carotene-linoleate as an inhibitor of lipid peroxidation (Ravindran et al, 2012). The effects of dietary phenolic compounds are of interest due to their antioxidant effects, their ability to hinder oxidative degradation of lipids, and their ability to enhance the nutritional value of food (Srivastava et al, 2013).…”
Section: Introductionmentioning
confidence: 99%